Modern computer architecture and organization : learn x86, ARM, and RISC-V architectures and the design of smartphones, PCs, and cloud servers - Ledin, Jim (Packt Publishing, 2022)
Are you a software developer, systems designer, or computer architecture student looking for a methodical introduction to digital device architectures, but are overwhelmed by the complexity of modern systems? This step-by-step guide will teach you how modern computer systems work with the help of practical examples and exercises. You'll gain insights into the internal behavior of processors down to the circuit level and will understand how the hardware executes code developed in high-level languages. This book will teach you the fundamentals of computer systems including transistors, logic gates, sequential logic, and instruction pipelines. You will learn details of modern processor architectures and instruction sets including x86, x64, ARM, and RISC-V. You will see how to implement a RISC-V processor in a low-cost FPGA board and write a quantum computing program and run it on an actual quantum computer. This edition has been updated to cover the architecture and design principles underlying the important domains of cybersecurity, blockchain and bitcoin mining, and self-driving vehicles. By the end of this book, you will have a thorough understanding of modern processors and computer architecture and the future directions these technologies are likely to take.
Includes index.
Keywords: Computer organization.; Computer architecture.; elektronické knihy; electronic books